Analisis kelayakan usaha tani kubis (Brassica Oleracea L.) di desa Beji Kecamatan Junrejo kota Batu - Yuhanin Zamrodah (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
The aim of this studies were to determine the efficiency or feasibility of cabbage farming income, income earned by farmers in one growing season. Research locations in Beji Village, Junrejo Subdistrict, the number of respondents were 30 cabbage farmers which were used as research samples. The data used primary data and secondary data. Method of analysis, namely the analysis of income Pd = TR - TC, analysis of costs TC = FC + VC, analysis of acceptance TR = Py. Y and analysis of the feasibility of R / C farming. The results obtained with a total revenue of Rp. 53,473,500.00; the variable cost is IDR 11,807,025.00; flat fee of IDR. 3,010,000.00; total cost of IDR. 14,817,025.00; the average income earned by cabbage farmers is IDR. 14,817,025.00; and obtained R / C value of 2.61 which means that each expenditure of IDR. 100.- will receive IDR. 261.00. Thus the cabbage farming in Beji Village is feasible to be cultivated because R / C> 1 means that the farming is profitable. Therefore, this farm is worth continuing.